Quality Assurance in the molecular diagnostic laboratory (Bangladesh Journal of Medical Microbiology, 2021)
Molecular diagnostics is currently playing an imperative role in the clinical microbiology laboratory. Quality assurance and quality control issues have often remained underdeveloped in our country and are still critical. To relate patient results to these, molecular diagnostics carry values in clinical diagnosis, therapeutic drug monitoring and remission and those results need to be comparable across time and methods. This may be achieved either by producing the identical value across methods and test versions or by using reliable and stable reference materials in the medical laboratories engaged with molecular tests. The establishment of international standards and reference materials, assessment and maintenance of technical competencies, regulatory oversight and best practices considerations are thus of utmost importance. This review focuses on general and specific issues relevant for quality assurance and quality control in the routine molecular diagnostics laboratory.Bangladesh J Med Microbiol 2021; 15 (1): 30-34